Effect of thermo-activation on mechanical strengths and chlorides permeability in pozzolanic materials - M. Elbar (Case Studies in Construction Materials, 2018)
The present research aimed to study the combined effects of natural pozzolana and curing on the compressive and flexural strengths of mortars; it also investigated the chloride permeability of concrete. To do that, Ordinary Portland cement (CEMI) was used and three concrete preparations were made by incorporating natural pozzolana at a rate of 10, 20 and 30% by weight of CEMI. Moreover, three curing methods were employed. The first one is a standard curing method, at temperature 20 °C, and 2 other thermo-activation methods at the temperatures of 40 °C and 70 °C, for a setting time of 4 h. The thermo-activation methods were used to accelerate the initial hydration, for the purpose of improving the strength of the prepared mortars and concretes at the early age. The results obtained indicate that, substituting natural pozzolana for CEMI with a level below 20% gives strengths comparable to those obtained with CEMI alone. The curing methods at 40 °C and 70 °C allowed increasing mortar and concrete strengths at the early age; however, it was found that the temperature of 70 °C reduces strengths, at later age. Natural pozzolana limits the penetration of chlorides. Keywords: CEMI, Pozzolana, Hydration, Strength, Temperature, Chlorides